2018
DOI: 10.1002/ece3.4242
|View full text |Cite
|
Sign up to set email alerts
|

The future of cold‐adapted plants in changing climates: Micranthes (Saxifragaceae) as a case study

Abstract: Research has shown species undergoing range contractions and/or northward and higher elevational movements as a result of changing climates. Here, we evaluate how the distribution of a group of cold‐adapted plant species with similar evolutionary histories changes in response to warming climates. We selected 29 species of Micranthes (Saxifragaceae) representing the mountain and Arctic biomes of the Northern Hemisphere. For this analysis, 24,755 data points were input into ecological niche models to assess both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Inclusion of landscape variables modestly improved model fit but did not contribute much to the models, a pattern consistent with a meta‐analysis of distribution models that found that temperature and precipitation often drive these models (Bradie and Leung 2017). In other cold‐adapted species, there is evidence that landscape factors may be important to distributions (Biella et al 2017, Stubbs et al 2018). In amphibians that are not cold adapted, distributions are related to land cover and climate, including positive interactions with certain types of human modification (Hartel and von Wehrden 2013, Préau et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of landscape variables modestly improved model fit but did not contribute much to the models, a pattern consistent with a meta‐analysis of distribution models that found that temperature and precipitation often drive these models (Bradie and Leung 2017). In other cold‐adapted species, there is evidence that landscape factors may be important to distributions (Biella et al 2017, Stubbs et al 2018). In amphibians that are not cold adapted, distributions are related to land cover and climate, including positive interactions with certain types of human modification (Hartel and von Wehrden 2013, Préau et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To date, research on Memecylon has mainly focused on its taxonomy, ethnobotany, and evolution (e.g., Amarasinghe, Joshi, et al, 2021;Bremer, 1988;Sivu et al, 2013) (Loarie et al, 2008;Manes et al, 2021;Thuiller et al, 2006) due to occupying specialized niches, limited dispersal capabilities, and reduced adaptive capacities when compared to nonendemic species (Chichorro et al, 2019;Staude et al, 2020). Further, organisms that have more restricted geographical ranges are at greater risk (Elsen & Tingley, 2015;Stubbs et al, 2018) compared to species with large geographical ranges, which may find refugia in parts of their range (Lucas et al, 2019). Therefore, we hypothesized that endemic Memecylon with restricted distribution ranges in Sri Lanka may be at more risk with climate change compared to nonendemics and species with large geographic ranges.…”
Section: Memecylon In Sri Lankamentioning
confidence: 99%
“…Climate models predict a likely global increase in temperature of 2°C by 2100 (IPCC 2014). The many negative effects of this increase will be particularly acute in arctic and alpine biomes (Pearson et al 2013), where all species are adapted to the naturally harsh climate (Stubbs et al 2018). Climate-change-related threats affecting the Arctic and the Alpine include the decrease of the predictability of weather patterns, permafrost melting, shrinking land cover due to rising sea levels, expansion of boreal forests and the resulting shrinkage of the tundra and polar desert, loss of relict species, and changes in trophic interactions (Corell 2006;Schmidt 2017).…”
Section: Introductionmentioning
confidence: 99%